Electrostatically driven resonance energy transfer in "cationic" biocompatible indium phosphide quantum dots. Issue 5 (27th March 2017) - Devatha, Gayathri; Roy, Soumendu; Rao, Anish; Mallick, Abhik; Basu, Sudipta; Pillai, Pramod P.
Abstract : InP QDs join the family of cationic nanoparticles as a practical alternative to toxic metal ion based QDs for biological applications. Abstract : Indium Phosphide Quantum Dots (InP QDs) have emerged as an alternative to toxic metal ion based QDs in nanobiotechnology. The ability to generate cationic surface charge, without compromising stability and biocompatibility, is essential in realizing the full potential of InP QDs in biological applications. We have addressed this challenge by developing a place exchange protocol for the preparation of cationic InP/ZnS QDs. The quaternary ammonium group provides the much required permanent positive charge and stability to InP/ZnS QDs in biofluids. The two important properties of QDs, namely bioimaging and light induced resonance energy transfer, are successfully demonstrated in cationic InP/ZnS QDs. The low cytotoxicity and stable photoluminescence of cationic InP/ZnS QDs inside cells make them ideal candidates as optical probes for cellular imaging. An efficient resonance energy transfer ( E ∼ 60%) is observed, under physiological conditions, between the cationic InP/ZnS QD donor and anionic dye acceptor. A large bimolecular quenching constant along with a linear Stern–Volmer plot confirms the formation of a strong ground state complex between the cationic InP/ZnS QDs and the anionic dye. Control experiments prove the role of electrostatic attraction in driving the light induced interactions, which can rightfully form the basis for future nano-bio studies between cationic InP/ZnS QDs and anionic biomolecules.